Analysis of Population Growth Projections on the Availability of Health Facilities in North Padang District, Padang City - putri, atika; Mariya, Sri (JURNAL BUANA, 2025)
The purpose of this study is to determine the population growth rate in North Padang District in 2021, find out the projected population growth and the need for health facilities in North Padang District and analyze the affordability of health facilities in North Padang District. This research uses quantitative descriptive method with documentation study approach, data obtained from the Central Statistics Agency (BPS) of Padang City. To analyze the reach of health facilities using the Network Analysis method. The results of the study are 1) The population growth rate in North Padang District has decreased significantly, as many as 71,112 people (2019) decreased to 55,171 people (2020). The number of puskesmas and pharmacies is in accordance with SNI. Meanwhile, the number of polyclinics has not been in accordance with SNI. 2) The projected population in 2031 is 55,517 people, meaning that it does not increase from the previous 10 years, namely in 2021 with 57,746 people. 3) for the radius of coverage of health facilities, puskesmas, polyclinics, and pharmacies, most of them can be reached from residential areas in North Padang District.